TEACHING MANAGEMENT SCIENCE IN PRE-SCHOOL EDUCATION METHODS OF FORMING THE METHODOLOGY - Shakhina Jabborova (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
In this article, management science is organized in preschool education complete information is given about each step. In addition, management is an urgent issue of today.